2014
DOI: 10.1186/1472-6874-14-46
|View full text |Cite
|
Sign up to set email alerts
|

Demand for long acting and permanent contraceptive methods and associated factors among married women of reproductive age group in Debre Markos Town, North West Ethiopia

Abstract: BackgroundEthiopia is the second most populous country in sub Saharan Africa with high total fertility rate, and high maternal and child mortality rates. In sub Saharan African countries, including Ethiopia, even though studies show that demand for contraception is high, the practice is low. Particularly, in Ethiopia, despite the fact that practices on long acting and permanent methods are believed to be low, there are limited evidences on the real magnitude of demand for the methods.MethodsTo assess demand fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
93
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 12 publications
23
93
7
Order By: Relevance
“…Regarding injectable 95.2%, followed by implants and IUD which were 91.5% and 88.7%, respectively. This result was consistent with finding from 2011 EDHS and research done in Butajira and Debre Markos which were 97% and 99%, respectively [8,14,16]. This study also showed that 88.2% of women had had awareness about LAPMs and 97.7%, 94.3% and 46.6% had awareness about implants, IUD, and female sterilization, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Regarding injectable 95.2%, followed by implants and IUD which were 91.5% and 88.7%, respectively. This result was consistent with finding from 2011 EDHS and research done in Butajira and Debre Markos which were 97% and 99%, respectively [8,14,16]. This study also showed that 88.2% of women had had awareness about LAPMs and 97.7%, 94.3% and 46.6% had awareness about implants, IUD, and female sterilization, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Current utilization of LAPMs found to be higher for implant 117(86.03%). This is in line with study done in Mekelle and Debre Markos; majority of women were used implants among current user of LAPMs which 87% and 81.2% [12,14]. The major source of LAPMs for the women was a public health facility (80.1%).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Women's decision to utilize contraception in Africa, depends on the support they get from their partners [28] [34] [36] [37].…”
Section: My Husband Would Not Get Upset If I Told Him That I Am Usingmentioning
confidence: 99%